Direct growth of Sb2Te3 on graphene by atomic layer deposition. Issue 50 (4th June 2015) - Zheng, Li; Cheng, Xinhong; Cao, Duo; Wang, Qian; Wang, Zhongjian; Xia, Chao; Shen, Lingyan; Yu, Yuehui; Shen, Dashen
<x xml:space="preserve">Abstract</x> Graphene can avoid the oxidation of Sb2Te3, eliminate the generation of an interface layer and maintain the crystal structures of Sb2Te3.